2010
DOI: 10.1111/j.1574-6941.2010.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Variation in permissiveness for broad-host-range plasmids among genetically indistinguishable isolates of Dickeya sp. from a small field plot

Abstract: Phytopathogenic populations need genetic flexibility to adapt to continually improving plant defences. The gene pool transferred by broad-host-range plasmids provides genetic variation for the population. However, a population has to balance this benefit with the risk of acquiring deleterious foreign DNA. This could be achieved by modulating the ratio of individuals with high or low permissiveness to broad-host-range plasmids. We investigated whether plasmid uptake varied among genetically indistinguishable is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 28 publications
3
15
0
Order By: Relevance
“…Transfer of an IncP-1 plasmid from E. coli to phylogenetically distant Flavobacteria was detected in soil microcosms (Pukall et al, 1996), indicating that transfer to distant nodes of the phylogenetic tree is not only possible, but also realized in undisturbed soil environments. In pure culture, permissiveness toward broad host range plasmids of isolates that are indistinguishable by 16S rRNA gene analysis can differ by more than 100-fold (Heuer et al, 2010). Here we confirm that inferring plasmid uptake and transfer frequency cannot be predicted based on the phylogenetic identity of an OTU.…”
Section: Resultssupporting
confidence: 68%
“…Transfer of an IncP-1 plasmid from E. coli to phylogenetically distant Flavobacteria was detected in soil microcosms (Pukall et al, 1996), indicating that transfer to distant nodes of the phylogenetic tree is not only possible, but also realized in undisturbed soil environments. In pure culture, permissiveness toward broad host range plasmids of isolates that are indistinguishable by 16S rRNA gene analysis can differ by more than 100-fold (Heuer et al, 2010). Here we confirm that inferring plasmid uptake and transfer frequency cannot be predicted based on the phylogenetic identity of an OTU.…”
Section: Resultssupporting
confidence: 68%
“…4) in two gammaproteobacterial species. Our empirical knowledge about plasmid host range is limited by the availability of model hosts, and can also be confounded by strain-and speciesspecific plasmid permissiveness (De Gelder et al, 2007;Heuer et al, 2007Heuer et al, , 2010. Future systematic host range analyses using additional model hosts will be important to strengthen the host-specialization hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty days after introducing the E. coli donor pTH16 and recipients into non-sterile soil, rhizosphere bacteria that captured the nourseothricin resistance plasmid were isolated and identified by BIOLOG as Agrobacterium , Pseudomonas and Flavobacterium . A similar approach was also taken to identify the host range of the IncP-1ε pHH3414 in soil microcosms planted with Acacia caven [63]. In this experiment soil bacteria that received pHH3414 were identified by 16S rRNA gene sequencing as Gammaproteobacteria ( Enterobacter amnigenus , Xanthomonas codiaei ) and Betaproteobacteria ( Cupriavidus campinensis , Alcaligenes sp.).…”
Section: Plasmid Host Range Determination and Plasmid Cost And Benmentioning
confidence: 99%
“…This was already known from matings in the laboratory [69], and is now confirmed for in situ plasmid spread. Additionally, it was shown that the permissiveness of a bacterial community and even of isolates to receive and maintain plasmids can change by several orders of magnitude in response to irregular environmental change such as manure fertilization [63,70]. …”
Section: Plasmid Host Range Determination and Plasmid Cost And Benmentioning
confidence: 99%